Oceanside dwelling for Mrs. Clinton Walker, sheet 7, work space and furniture - Frank Lloyd Wight:::::::::
Drawing which Mills traced from Frank Lloyd Wright's original design for the Walker residence, with additions contributed by Mills for his project on the residence. Includes details on the loggia doors and note on linoleum installation.